PENGARUH PSIKOEDUKASI TERHADAP PERILAKU ORANG TUA DALAM MERAWAT ANAK KRITIS DI PEDIATRIC INTENSIVE CARE UNIT RSUP Dr. SARDJITO YOGYAKARTA - Sari, Ignasia Yunita (STIKES Bethesda Yakkum, 2017)
Parents’ crisis situation resulting from condition of children treated in Pediatric Intensive Care Unit (PICU) hinders the parents’ role in taking care of their children. Psycho education can decrease the stress to increase the parents’ role in supporting their children’s treatment. This research was to find out the effect of psycho education on parents’ attitude in taking care of children with critical condition in PICU. Quasi experimental research was used with pre-test post-test without control. Population was parents whose children were hospitalized in PICU of RSUP Dr. Sardjito Yogyakarta. Consecutive sampling technique resulted 37 parents who met the criteria. The independent variable was psycho education, the dependent variable was parents’ attitude in taking care of their children with critical condition. The test was done by doing observation by observer who has done observation reliability test using cohen cappa resulted between 0,60-0,73 (good). The data analysis used Wilcoxon Sign Rank Test with 95% confidence interval. The result showed an effect of psycho education on parents’ attitude in taking care of children with critical condition in PICU.